1997
DOI: 10.1007/s004670050348
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteric reflux in the newborn: relationship to fetal renal pelvic diameter

Abstract: There has been a low yield of primary vesicoureteric reflux (VUR) from screening the fetal urinary tract during obstetric sonography. We sought to determine whether changing the cut-off level of fetal renal pelvic diameter from 10 mm to 4 mm would improve the yield of VUR. In a prospective community-based study, a fetal renal pelvic diameter of 4 mm or more on a transverse view of the fetal renal hilum at obstetric sonography after 16 weeks' gestation was found in 426 fetuses from 9,800 consecutive pregnancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…We undertook a systematic review and metaregression analysis of cohort studies that reported outcomes of fetal RPD, for fetuses with an RPD of 諈15 mm. The primary analyses were based on fetuses identified by routine fetal ultrasound screening (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Secondary analyses evaluated studies that included pregnancies referred for specialist obstetric/fetal medicine reasons (29 -34).…”
Section: To Screen or Not To Screen That Is The Question: Whether 'mentioning
confidence: 99%
See 1 more Smart Citation
“…We undertook a systematic review and metaregression analysis of cohort studies that reported outcomes of fetal RPD, for fetuses with an RPD of 諈15 mm. The primary analyses were based on fetuses identified by routine fetal ultrasound screening (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Secondary analyses evaluated studies that included pregnancies referred for specialist obstetric/fetal medicine reasons (29 -34).…”
Section: To Screen or Not To Screen That Is The Question: Whether 'mentioning
confidence: 99%
“…Five hundred and six potentially relevant studies were identified, of which 18 met the inclusion criteria (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Two studies reported overlapping patient cohorts but different outcomes (27,28).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous retrospective studies, all of which had incomplete follow-up or postnatal investigation, or included children with additional renal abnormalities, have demonstrated a poor correlation between VUR and the degree of pelviectasis on postnatal US [10,11,12,13,14].A more-recent prospective study, with VCUG performed in all children, suggested that two separate normal US scans in the first 6 weeks postnatally were sufficient to exclude VUR in 93% of cases [15]. However, this study included children with additional renal abnormalities, so that the true prevalence of primary VUR in infants with isolated ANH remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Fetal renal pelvis dilatation on obstetric sonography is a common finding, seen in up to 3% of obstetric sonograms [1]. The relative prevalence of vesicoureteral reflux (VUR) or obstructive uropathy in infants investigated postnatally seems to depend on the postnatal investigative protocol.…”
Section: Introductionmentioning
confidence: 99%